Pengaruh Penggunaan Quipper School Terhadap Hasil Belajar Siswa Pada Mata Pelajaran IPA di SMP Negeri 1 Bissappu Kabupaten Bantaeng - Mawar; Nasir; Akram (Jurnal Pendidikan dan Pembelajaran, 2022)
The purpose of this study was to determine the effect of the use of Quipper Shool on student learning outcomes in science subjects on the human digestive system. Class VIII A students at SMP Negeri 1 Bissappu in the academic year 2022/2023, totaling 18 students. This research is a type of quantitative research using experimental methods as well as the media used in the study, namely Quipper School. The population in this study were all students of class VIII and class VIII A as the sample. The instrument in this study provided pre and post-test on the sample. Data collection techniques used are observation, tests, and documentation. Techniques Data analysis is descriptive statistical analysis and inferential statistical analysis. Based on the results of research and data analysis regarding comparison of statistical scores, comparison of learning outcomes categories, and comparison of completeness levels, it has been proven that there is an increase in student learning outcomes in class VIII A of SMP Negeri 1 Bissappu. It can be seen that student learning outcomes through descriptive statistical analysis before using Quipper School media, student scores. below the KKM value and after using the Quipper School media the student's score increased above the KKM score. It is known that the posttest score of 80.14 is greater than the pretest score of 76.14. From the results of these data, it can be concluded that the Quipper School-based learning media in learning can have an influence on student learning outcomes in science subjects for class VIII A SMP Negeri 1 Bissappu and provide a positive response to the learning media.